Immune Response of Multiparous Hyper-Immunized Sows against Peptides from Non-Structural and Structural Proteins of PRRSV - Edgar Rascón-Castelo; Alexel Burgara-Estrella; Mónica Reséndiz-Sandoval; Andrés Hernández-Lugo; Jesús Hernández (Vaccines, 2015)
The purpose of this study was to evaluate the humoral and cellular responses of commercial multiparous and hyper-immunized sows against peptides from non-structural (nsp) and structural proteins of porcine reproductive and respiratory syndrome virus (PRRSV). We selected sows with different numbers of parities from a commercial farm. Management practices on this farm include the use of the MLV commercial vaccine four times per year, plus two vaccinations during the acclimation period. The humoral response was evaluated via the antibody recognition of peptides from nsp and structural proteins, and the cellular response was assessed by measuring the frequency of peptide and PRRSV-specific IFN-gamma-secreting cells (IFNγ-SC). Our results show that sows with six parities have more antibodies against peptides from structural proteins than against peptides from nsp. The analysis of the cellular response revealed that the number of immunizations did not affect the frequency of IFNγ-SC and that the response was stronger against peptides from structural proteins (M protein) than against nsp (nsp2). In summary, these results demonstrate that multiparous, hyper-immunized sows have a stronger immune humoral response to PRRSV structural peptides than nsp, but no differences in IFNγ-SC against the same peptides were observed.